2023
DOI: 10.2147/tacg.s412364
|View full text |Cite
|
Sign up to set email alerts
|

Profile of BRAFV600E, BRAFK601E, NRAS, HRAS, and KRAS Mutational Status, and Clinicopathological Characteristics of Papillary Thyroid Carcinoma in Indonesian National Referral Hospital

Agnes Stephanie Harahap,
Imam Subekti,
Sonar Soni Panigoro
et al.

Abstract: Introduction BRAF V600E and RAS mutations are the most common gene mutations in papillary thyroid carcinoma (PTC) that may be correlated with its biological behavior. There are still limited data about BRAF V600E and RAS mutations in Indonesia. This study aims to determine the prevalence of BRAF V600E and RAS mutations, and their association with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…According to the multivariate analysis, nodule size, microcalcifications, and BRAF V600E mutations were all independently related with LN metastasis [24]. In addition, a study in Indonesia by Harahap et al (2023) concluded that BRAF V600E was associated with LN metastasis in PTC patients. They reported a significant association between BRAF V600E mutation with advanced clinical stage, tall cell variant of PTC, lymphovascular invasion, non-encapsulated morphology, and extrathyroidal extension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the multivariate analysis, nodule size, microcalcifications, and BRAF V600E mutations were all independently related with LN metastasis [24]. In addition, a study in Indonesia by Harahap et al (2023) concluded that BRAF V600E was associated with LN metastasis in PTC patients. They reported a significant association between BRAF V600E mutation with advanced clinical stage, tall cell variant of PTC, lymphovascular invasion, non-encapsulated morphology, and extrathyroidal extension.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study at Dr. Cipto Mangunkusumo Hospital to investigate the TERT rs2853669 mutation and its association with the occurrence of LN metastases. Furthermore, this work builds on a recent study by Harahap et al (2023), which investigated the link between BRAF V600E mutation and clinicopathological characteristics of PTC. A prior study by Perdana et al linked BRAF mutation to the chance of thyroid nodule malignancy based on cytology results, however it used cytological samples from a fine-needle aspiration biopsy (FNAB) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRAF mutation was associated with a lower HT incidence, a higher capsular invasion rate, and CPTC, a result that is 30 Comparison of the clinicopathologic features of BRAF V600E -mutated PTC with those of RAS-mutated PTC showed that BRAF V600E mutation was significantly associated with a lower incidence of HT and a higher rate of thyroid capsular invasion, suggesting that PTC with BRAF V600E mutation tends to exhibit a more aggressive behavior, a finding that aligns with prior studies. 31,32 There are also conflicting findings in previous studies regarding the relationship between mutations and clinicopathological factors; for example, some meta-analyses reported associations between BRAF V600E mutation and factors such as tumor multifocality, thyroid capsular invasion, ETE, LNM, and advanced stage, 33,34 while another study found no association between BRAF mutations and any clinicopathological factors. 35 Alternatively, the same mutations, including BRAF V600E , may be associated with various clinicopathological factors in different studies.…”
Section: Discussionmentioning
confidence: 99%